Generalized trace pseudo-spectrum of matrix pencils - Aymen Ammar; Aref Jeribi; Kamel Mahfoudhi (Cubo, 2019)
The objective of the study was to investigate a new notion of generalized trace pseudo-spectrum for an matrix pencils. In particular, we prove many new interesting properties of the generalized trace pseudo-spectrum. In addition, we show an analogue of the spectral mapping theorem for the generalized trace pseudo-spectrum in the matrix algebra.